Bovine Jugular Vein Conduit: A Mid- to Long-Term Institutional Review. Issue 5 (September 2018) - Patel, Parth M.; Tan, Corinne; Srivastava, Nayan; Herrmann, Jeremy L.; Rodefeld, Mark D.; Turrentine, Mark W.; Brown, John W.
Background: Since 1999, we have used the bovine jugular vein conduit for right ventricular outflow tract reconstruction in infants and children. Herein, we review their mid- to long-term outcomes. Methods: Between 1999 and 2016, 315 bovine jugular vein conduits were implanted in 276 patients. Patients were grouped by age at bovine jugular vein conduit implant: group 1: 0 to 1 years (N = 65), group 2: one to ten years (N = 132), and group 3: older than ten years (N = 118). For survival and hemodynamic analysis, additional group stratification was done based on conduit size. Group small: 12 and 14 mm (N = 75), group medium: 16 and 18 mm (N = 84), and group large: 20 and 22 mm (N = 156). Results: Mean follow-up for groups 1, 2, and 3 was 4.0, 4.9, and 5.9 years, respectively. Early mortality was 9%, 0%, and 1% for groups 1, 2, and 3, respectively ( P < .001). Late mortality was 5%, 2%, and 2% for groups 1, 2, and 3, respectively ( P = .337). Group 1 had the lowest ten-year freedom from conduit failure at 13%, versus 53% and 69% for groups 2 and 3, respectively ( P < .001). A total of 21 (6.6%) patients developed endocarditis, 11 (3.5%) patients required reoperation, and 10 (3.2%) patients required antibiotic therapy alone. Conclusions: The bovine jugular vein conduit is a useful option for right ventricular outflow tract reconstruction given its easy implantability and acceptable midterm durability.